Evaluasi dan Perbaikan Pengalaman Pengguna Aplikasi "cQuran" Menggunakan Metode Usability Testing dan Design Thinking - Gilang Nur A'idi; Lutfi Fanani; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
cQuran was a platform for Al-Quran recitation session, together using voice channel feature that developed in mobile apps. Users could create a voice channels with selected surah. Through this channel, user can start recitation session with other users, as well as interact to provide input from the recitation of the Al-Quran that is spoken. In the process of developing the application, the development team has never been evaluated the app related to the user experience. In this study, evaluation was carried out and improvement were designed to enhance the user experience related to the user interaction with the application. In the process, the Usability Testing method is used with 3 aspects, namely effectiveness, efficiency, and satisfaction, as well ass design thinking the process of designing the solution. Based on the results of the first stage evaluation, for the effectiveness aspect it was obtained a value of 67,85%, 33,72% for efficiency aspect, and a SUS score for the satisfaction aspect for 69. Based on the results of the first stage evaluation, there were 17 recommendation points based on observations and interviews. Using that recommendations, an improvement was designed for cQuran apps. After carrying out the second phase of testing the effectiveness value was 92%, the efficiency aspect was 76%, and SUS score for the satisfaction aspect was 75. Based on the student t-test that conduct to test the truth of the increase in the third usability aspect, it shows that the increased value was really happen. For the efficiency aspect that get a higher increased percentage namely 42,3%, could occur after the addition of a onboarding screen and tutorial tooltips flow. It makes user to be able to learn all of the features and new layout design that implemented in the solution.